Cultivating Early Childhood Character Through Geoffrey Leech's Politeness Maxims; a Case Study and Innovative Design - Nahdi, Khirjan; Al-Pansori, Muh. Jaelani (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
The purpose of this study is to 1) reveal the maxim form in early childhood teacher-student communication in communication in the educational environment (school); 2) find aspects of character that are formed through the maxim of politeness displayed, both teacher to student, student to teacher, and student to student, as an alternative to early childhood learning design. Data collection through open questionnaires is related to a) the form of communication delivered by teachers as messengers and students as recipients of messages; b) the situation of message delivery, directive or otherwise; and c) the character to be developed. Data analysis with stages: a) grouping communication based on the maxim of politeness. b) grouping communication situations according to their respective forms. It is concluded that there are six maxims of politeness, namely 1) the maxim of politeness of wisdom/wisdom with the substance of giving by not taking advantage of themselves but benefiting the interlocutor; 2) the maxim of politeness generosity, with substance giving by sharing equally between speakers and interlocutors; 3) maxim of politeness of appreciation, with the substance of the work or deeds of the interlocutor; 4) maxim of simplicity, with the substance of the interlocutor and speaker balancing tendencies with one's capacity; 5) maxim of consensus politeness, with the substance of agreeing with the offer of the interlocutor according to the context he is experiencing; and 6) the maxim of politeness, sympathy, with the substance of responding or accepting others reasonably with the awareness that everyone can experience the context.